2009
DOI: 10.1016/j.ajic.2008.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Staffing and structure of infection prevention and control programs

Abstract: Background-The nature of infection prevention and control is changing; however, little is known about current staffing and structure of infection prevention and control programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 22 publications
5
78
0
5
Order By: Relevance
“…In a recent survey of 289 hospitals participating in the NHSN, registered nurses led 66% of infection control programs, and physicians led only 12% of programs. Of those programs with hospital epidemiologists (49% of programs), the majority were physicians, but only 10% reported working full time as a hospital epidemiologist (315). These findings coupled with results of the SENIC study and an ever-expanding and more complex health care system suggest a great need for hospital epidemiologists in order to achieve significantly lower rates of HAIs.…”
Section: The Hospital Epidemiologistsupporting
confidence: 59%
See 3 more Smart Citations
“…In a recent survey of 289 hospitals participating in the NHSN, registered nurses led 66% of infection control programs, and physicians led only 12% of programs. Of those programs with hospital epidemiologists (49% of programs), the majority were physicians, but only 10% reported working full time as a hospital epidemiologist (315). These findings coupled with results of the SENIC study and an ever-expanding and more complex health care system suggest a great need for hospital epidemiologists in order to achieve significantly lower rates of HAIs.…”
Section: The Hospital Epidemiologistsupporting
confidence: 59%
“…Many professional organizations offer training courses in surveillance and infection control, and many IPs are obtaining certification in infection control by the Certification Board of Infection Control (293). A recent survey by Stone et al found that IPs spend the majority of their time collecting and analyzing data (315). This suggests that less time 164 SYDNOR AND PERL CLIN.…”
Section: Infection Preventionistsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the development of medical science and the changes in medical models, management of hospital-acquired infections has become a systemic program, requiring the involvement of all doctors, nurses, and laboratory, service, and administrative staff (Griffiths et al, 2009;Stone et al, 2009). Control of hospital-acquired infection has also become an important reflection on the level of medical technology and the service quality of hospitals (Gao, 2008).…”
Section: Introductionmentioning
confidence: 99%